Analisis Kebijakan Tentang Relevansi Kebijakan Perencanaan Pembangunan Daerah Dengan Rangkaian Kegiatan Riset Pemerintah Kota Surakarta - Didik Setiyawan; Rizky Nikma (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2023)
The 2017-2045 National Research Master Plan (RIRN) sets the vision of "Research-Based Competitive and Sovereign Indonesia 2045". Competitiveness means that research is the main motor for producing inventions and innovations that have an impact on increasing the nation's competitiveness. Research-based sovereignty means that RIRN is the starting point for forming a socio-economically independent Indonesia through mastery and high competitive advantage of science and technology globally1. This vision is described in two missions, namely (1) creating an innovative Indonesian society based on science and technology; and (2) creating a research-based global competitive advantage for the nation. The objectives of the 2017-2045 RIRN are: increasing society's science and technology literacy, increasing Indonesia's research capacity and competence in the global realm, and improving the science and technology-based economy.